Impact of Lipoprotein(a) on Valvular and Cardiovascular Outcomes in Patients With Calcific Aortic Valve Stenosis - Arnaud S. Girard; Audrey Paulin; Hasanga D. Manikpurage; Emma Lajeunesse; Marie‐Annick Clavel; Philippe Pibarot; John H. Krege; Patrick Mathieu; Sébastien Thériault; Benoit J. Arsenault (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Lp(a) (lipoprotein(a)) is an independent risk factor for calcific aortic valve stenosis (CAVS). Whether patients with CAVS and high Lp(a) levels are at higher risk of valvular or cardiovascular events is unknown. The aim of this study is to determine whether higher Lp(a) levels are associated with valvular and cardiovascular outcomes in patients with CAVS. Methods and Results We identified 1962 patients from the UK Biobank with an electronic health record or self‐reported CAVS diagnosis but who did not previously undergo aortic valve replacement (AVR) and had a minimal follow‐up time of 2.5 years. Cox proportional hazard regression was used to evaluate the effect of Lp(a) on AVR, AVR or cardiac death, and valvular or cardiovascular events (AVR, cardiac death, myocardial infarction, stroke, heart failure, or coronary artery bypass grafting). The maximal follow‐up time was set to 5 years. During the follow‐up, 198 patients underwent AVR, 260 had AVR or cardiac death, and 435 had at least 1 valvular or cardiovascular event. Patients with Lp(a) levels ≥125 versus <125 nmol/L were at higher risk of AVR (hazard ratio [HR], 1.58 [95% CI, 1.17–2.12]), AVR or cardiac death (HR, 1.43 [95% CI, 1.10–1.86]), and cardiovascular or valvular events (HR, 1.36 [95% CI, 1.11–1.68]). Point estimates were comparable in men versus women, younger versus older patients, and in patients with higher versus lower plasma C‐reactive protein levels. Conclusions In patients with CAVS, Lp(a) levels predicted a higher risk of valvular and cardiovascular outcomes. The impact of Lp(a)‐lowering therapies on valvular and cardiovascular health should be assessed in a long‐term randomized clinical trial.